The Effect of Ratio of Fiber Bundles in the Textile Composite Layer - Bojtár Gergely (Journal of Mechanical Engineering, 2024)
The article shows how the orthotropic material properties of the textile composite layer change if the ratio of longitudinal and transversal fiber bundles in the textile is modified in the case of a composite reinforced with plain weave textile. I determine the material properties using model-cell and finite element simulation. The density of the longitudinal fiber bundles is the same in each of the five examined layer models. I change the ratio of the fiber bundles of the textile by varying the distance of the transversal roving’s in each model.